2021
DOI: 10.2147/phmt.s306475
|View full text |Cite
|
Sign up to set email alerts
|

Full Vaccination Coverage and Associated Factors Among 12-to-23-Month Children at Assosa Town, Western Ethiopia, 2020

Abstract: Introduction: Vaccination means the injection of a killed microbe to stimulate the immune system against the microbe, which prevents communicable diseases. It's the most important and cost-effective public health intervention to reduce child mortality and morbidity. Ethiopian national full vaccination coverage is 43%. This research aimed to assess full vaccination coverage and associated factors among 12-to-23-month children at Assosa Town. Methods: A community-based cross-sectional study was conducted among c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…The finding was consistent with studies done in Assosa town. 29 In fact, in the early stages of the COVID-19 pandemic, this could be due to the risk of infection and the need to keep a physical distance. Stay-at-home and social distancing strategies reduce children’s access to routine immunization services, putting them at risk for vaccine-preventable diseases and their complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding was consistent with studies done in Assosa town. 29 In fact, in the early stages of the COVID-19 pandemic, this could be due to the risk of infection and the need to keep a physical distance. Stay-at-home and social distancing strategies reduce children’s access to routine immunization services, putting them at risk for vaccine-preventable diseases and their complications.…”
Section: Discussionmentioning
confidence: 99%
“…The finding was consistent with studies done in Zimbabwe, the national level of Ethiopia, Wogera, Ambo, Sekota, Wonago, Dessie, and Asossa. 8 , 12 , 21 , 22 , 29 , 31 , 37 , 43 This could be due to the fact that women who attend ANC follow-up may receive postnatal counseling on child immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 The other study conducted in Ethiopia agreed with our finding indicating that the odds of full vaccination in a child early in its second year was 2.7 times higher than later in its second year (AOR: 2.7, 95% CI [1.36, 5.4]). 42 This may be due to vaccine coverage increasing from time to time or respondents recalling recent vaccination status that corresponds to younger children more than older children.…”
Section: Discussionmentioning
confidence: 99%
“…The highest coverage of full vaccination in Addis Ababa (83%) and lowest in Afar region due to different challenges and opportunities as explained in other studies (20%) (5,13). Studies have also reported that maternal education, place of delivery, antenatal care (ANC) visits, postnatal care follow up, place of residence and exposure to mass media as predictors of poor child immunization status (13,14,17,19). However, most of the studies were cross-sectional and failed to include certain variables or factors that could be pertinent in the Ethiopian context, such as socioeconomic status, attitude and service satisfaction towards immunization services provision at grassroots of individual family members and few community-based studies are available.…”
Section: Introductionmentioning
confidence: 90%